Owl pellets: a wise DNA source for small mammal genetics. (17th August 2015) - Guimaraes, S.; Fernandez‐Jalvo, Y.; Stoetzel, E.; Gorgé, O.; Bennett, E. A.; Denys, C.; Grange, T.; Geigl, E.‐M.
Abstract: Pellets of raptors are an important source for the study of the taxonomy, phylogeography and ecological diversity of small vertebrates. Since birds of prey are efficient collecting agents for both rare species and those reluctant to enter traps, they offer an important complement to traditional trapping efforts in the field. The possibility of using bones and teeth recovered from pellets as a convenient alternative DNA source for genetic studies requires a more complete understanding of the DNA preservation of these partially digested remains. It is not yet clear, for example, to which degree DNA is preserved and how heterogeneous DNA preservation is in the different skeletal remains found in pellets since systematic quantitative analyses are missing. Here, we attempt to improve this knowledge by quantifying the degradation of DNA during the digestion process of raptors using 62 individual rodent bones and teeth from different pellets. We show a very high variability in DNA preservation between bones. Interestingly, variability between bones within the same pellet is much higher than that found between pellets, which has major consequences for genetic studies as it implies that bones from the same pellet that could belong to different individuals/species should be tested individually when multiple markers are analyzed. We find that neither the identity of the skeletal part nor microscopic observation of the degree of digestion are useful proxies for DNA preservation, and we thus recommend the use of screening strategies to identify the most suitable bones to include in analyses. We conclude that pellets of owls, whether freshly collected or from natural history collections, can be a practical noninvasive source for genetic studies of small vertebrates provided the design of the study takes into account the short DNA molecule length, the low quantity of DNA preserved and the heterogeneity in DNA preservation.